Constructions of Spectrally Null Constrained Complete Complementary Codes via the Graph of Extended Boolean Functions - Shen, Bingsheng; Yang, Yang; Zhou, Zhengchun; Mesnager, Sihem (IEEE transactions on information theory, 2023)
Complete complementary codes (CCCs) have important applications in communication, radar, and information security. In modern communication and radar systems, certain spectrum is reserved or prohibited from transmission, which leads to the so-called spectrally null constrained (SNC) problem. Compared with vast works on conventional CCCs, relatively little is known about SNC-CCCs. One objective of this paper is to derive several constructions of CCCs with more flexible settings from the graph of extended Boolean functions. This generalizes earlier achievements on CCCs from recent literature. Another objective of this paper is to employ the graphs of extended Boolean functions and polynomial representation of sequences to construct SNC-CCCs.